Energy-storage properties of Bi0.5Na0.5TiO3-BaTiO3-KNbO3 ceramics fabricated by wet-chemical method. Issue 1 (January 2017) - Xu, Qi; Xie, Juan; He, Zichen; Zhang, Lin; Cao, Minghe; Huang, Xindi; Lanagan, Michael T.; Hao, Hua; Yao, Zhonghua; Liu, Hanxing
Abstract: 0.93Bi0.5 Na0.5 TiO3 -0.07BaTiO3 (BNTBT) and KNbO3 (KN) powders with average particle size of ∼50 nm and ∼300 nm were synthesized by sol-gel method and hydrothermal method, respectively. Then, (1 − x)(BNTBT)-xKN (BNTBT-KN, x = 0, 0.01, 0.03, 0.05, 0.07) ceramic samples were prepared using these two powder precursors. The structure, dielectric and energy-storage properties of BNTBT-KN ceramics were comprehensively investigated. All the ceramic samples were in single perovskite structure, indicating that KN can completely dissolve into BNTBT within the studied composition range. BNTBT-KN ceramics exhibited a high dielectric constant at room temperature, being in the order of 1430–1550. Ferroelectric hysteresis loops at room temperature became more slim with the increase of KN content, which largely improved energy-storage density and efficiency. For the composition of x = 0.05, the maximum recoverable energy-storage density reached 1.72 J/cm 3 under 16.8 kV/mm, which is superior to linear dielectrics and even some Pb-based systems. All these results demonstrate that 0.95BNTBT-0.05KN fabricated by wet-chemical method is a promising lead-free dielectric material for energy-storage capacitors.